Gender Differences in Cardiovascular Risk Profile in Rheumatoid Arthritis Patients with Low Disease Activity. (28th March 2019) - Targońska-Stępniak, Bożena; Biskup, Małgorzata; Biskup, Wojciech; Majdan, Maria
Abstract : Objective . Patients with rheumatoid arthritis (RA) have an excess risk of cardiovascular (CV) disease (CVD). The objective of the study was to compare CV risk profile in female and male RA patients with low disease activity. Materials and Methods . The study group consisted of 70 RA patients with continuous low disease activity and no CVD (54 women, 16 men) and 33 healthy controls of comparable age. The groups were assessed for blood pressure, serum amino-terminal pro-brain natriuretic peptide (NT-proBNP), carotid intima media thickness (cIMT), electrocardiography, ejection fraction (EF), and diastolic dysfunction (DD). Results . Significantly higher burden of atherosclerosis, as revealed by higher cIMT, was found in males [0.93 (0.2) mm] vs females [0.80 (0.2) mm]. The risk of 10-year CVD was significantly higher in men than in women with RA. High/very high risk of fatal CVD was found in 62.5% of male patients. Males were significantly more often current/ex-smokers and had lower HDL-cholesterol and higher atherogenic index. There were no significant differences in NT-proBNP, QTc duration, and parameters of EF and DD. Conclusions . In RA patients with continued low disease activity, a higher burden of atherosclerosis was found in males than in females. The data suggest a significant impact of traditional CV risk factors.